PENGARUH MOTIVASI DAN KOMITMEN TERHADAP PRESTASI KERJA PEGAWAI DINAS PERIZINAN DAN PENANAMAN MODAL DAERAH ISTIMEWA YOGYAKARTA (DPPM DIY) - Savera Mahenina Juanita; Didik Subiyanto; Ignatius Soni Kurniawan (Program Studi Manajemen, 2021)
This study aims to determine the effect of motivation and commitment on employee work performance. This type of research used in this research is quantitative research. The population in this study were all employees of the Yogyakarta Special Region Licensing and Investment Service (DPPM DIY), both permanent and contractual. The number of samples taken in this study were 50 employees. The results of this study indicate that the effect of motivation has a positive and significant effect on work performance, commitment has a positive and significant effect on work performance, and motivation and commitment have a positive and significant effect on work performance of the employees of the Licensing and Investment Service of the Special Region of Yogyakarta (DPPM DIY).